L’invention du Vieux‑Montréal. Les représentations d’un quartier historique dans les guides touristiques (19e‑20e siècles) - Drouin, Martin (Revue d'histoire de la Nouvelle-France, 2023)
Keywords: Patrimoine; Quartiers; Tourisme; Vieux-Montréal

Des origines à la Dépression. Quartier Crawford Park- (Partie 2) - Voisine, John (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2023)
Keywords: Quartiers; Verdun

Sur les pas d’Oscar et d’Oliver dans la Petite-Bourgogne. Première partie : Vie associative dans le quartier - Willis, John (Cap-aux-Diamants, 2023)
Keywords: Petite-Bourgogne; Quartiers

Service d'urbanisme, 1941-1951. Le District 11, quartiers Ahuntsic et Villeray, à l'époque des grandes transformations - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Keywords: Ahuntsic; Quartiers; Villeray

Les quartiers de la grande bourgeoisie: le cas du Golden Square Mile à Montréal - Bérubé, Harold (Histoire des villes nord-américaines, 2022)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

Petites et grandes boulangeries. La fabrication du pain dans le quartier Centre-Sud de Montréal - Giroux, Éric (Cap-aux-Diamants, 2021)
Keywords: Alimentation; Boulangerie; Centre-sud (quartier)

Histoire de la Côte-des-Neiges: 325 années de métamorphose - Rousseau, Sylvain (Sylvain Rousseau, 2023)
Keywords: Côte-des-Neiges; Quartiers

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

The Death of the Golden Square Mile? Understanding the Transformation of an Urban District, 1945-1985 - Bérubé, Harold (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Golden Square Mile; Quartiers

Proprety and Power: Connecting the Dots - Olson, Sherry (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

Montreal's Square Mile: the making and transformation of a colonial metropole - Anastakis, Dimitry; Kirkland, Elizabeth; Nerbas, Don (University of Toronto Press, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

The High Ground: Mansions, Mythology, and the Mountain - Macleod, Roderick (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Paysages; Quartiers

La naissance du quartier de la Poudrière (1) - Clairoux, Benoit (Les Argoulets, 2024)
Keywords: Armes; Femmes; Guerre; Verdun

Cartierville 1954-2024. Du Parc Belmont à un projet de Quartier culturel - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2024)
Keywords: Cartierville; Chanson; Musique

En 1909 découverte d'une voûte mystérieuse dans le quartier Rosemont - Gouin, Christiane (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Keywords: Rosemont

Les ateliers d’histoire, issus de l’action citoyenne au coeur des quartiers montréalais - Carbonneau, Réjean (Cap-aux-Diamants, 2022)
Keywords: Atelier d'histoire d'Hochelaga-Maisonneuve; Histoire

La requalification du patrimoine à l'échelle du quartier à Montréal : les anciens théâtres-cinémas et le cas du théâtre Rialto - Giulia, Verticchio (Université du Québec à Montréal, 2020)
Keywords: Cinéma; Patrimoine; Théâtre

La rue Saint-Hubert et sa plaza - Bur, Justin (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2023)
Keywords: Saint-Hubert (rue)

La conservation, approche centrale de l’identité renouvelée et célébrée du parc Jean-Drapeau - Cha, Jonathan (Journal of the Society for the Study of Architecture in Canada / Journal de la société pour l'étude de l'architecture au Canada, 2023)
Keywords: Conservation; Parcs; Patrimoine; Île Sainte-Hélène

L'avenue du Parc et son histoire: témoin privilégié de la diversité montréalaise - Desjardins, Yves (Les éditions du Septentrion, 2023)
Keywords: Mile End; Rues

La traversée du bois de Saraguay - Lauzon, Gilles (Paysages du mouvement/paysages en mouvements: Trajectoires, perspectives et panoramas, 2021)
Keywords: Parcs; Saraguay

La Côte à Baron (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2024)
Keywords: Baron (côte à); Flore; Jardins; Plateau Mont-Royal

Le Bois de Saraguay - Poitras, Jean (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Keywords: Conservation; Faune; Flore; Parcs; Patrimoine

Village de Saint-Jean-Baptiste. 160e anniversaire (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2022)
Keywords: Saint-Jean-Baptiste (village); Villages

Bref regard sur la paroisse Saint-Jean-Vianney - Gouin, Christiane (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2021)
Keywords: Saint-Jean Vianney (paroisse)

La Côte-de-Saraguay - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Côtes; Saraguay; Villages

L'implantation des paroisses au village de Côte Saint-Louis - Laperrière, Guy (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2021)
Keywords: Côtes; Protestants; Saint-Enfant-Jésus-du-Mile End (paroisse); Saint-Jean-Baptiste (paroisse); Villages; Églises

Côte Saint-Louis. 175e anniversaire (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2021)
Keywords: Côtes; Maires; Parcs; Rues; Tannerie; Villages

De Lorimier 1895-1909 (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
Keywords: Chaussure; De Lorimier (village); Parcs; Usines Angus

Le mystère urbain de Crawford Park. Des origines à la Dépression- (Partie 1) - Voisine, John (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2023)
Keywords: Quartiers; Verdun

Jobs, Homes, and the Right to Exist: Neighbourhood Activism in Deindustrializing Toronto and Montreal, 1963-1989 - Vickers, Simon (Université de Toronto, 2021)
Keywords: Quartiers; Travail

L'avenue du Mont-Royal (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2024)
Keywords: Magasins; Mont-Royal (rue); Plateau Mont-Royal; Tremblay, Michel

« Glad of your help »: Scottish Architects in Montreal, 1860-1940 - Adams, Annmarie (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Golden Square Mile; Royal Victoria Hospital; Écossais

Le Plateau industriel (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
Keywords: Alimentation; Chaussure; Grèves; Plateau Mont-Royal (arrondissement); Travail; Vêtements

Gestion publique des personnes en situation de marginalité à Montréal. Quelques repères historiques - Parazelli, Michel; Bourbonnais, Mathieu (Itinérance et cohabitation urbaine. Regards, enjeux et stratégies d'action, 2021)
Keywords: Faubourgs; Itinérance; Pauvreté; Quartier des spectacles; Quartiers; Saint-Laurent (quartier)

Passé et avenir d'une rivière montréalaise - Legault, Louise (Histoire Québec, 2024)
Keywords: Lachine; Lachine (canal); Pollution; Égouts

Le mystère de Crawford Park-(Partie 3) - Voisine, John (Les Argoulets, 2024)
Keywords: Logement; Quartiers; Verdun

The “Normalized Quiet of Unseen Power”: Recognizing the Structural Violence of Deindustrialization as Loss - High, Steven (Urban History Review / Revue d'histoire urbaine, 2021)
Keywords: Pointe-Saint-Charles; Quartiers

Gros plan sur la rue Masson (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2020)
Keywords: Quartiers; Rosemont; Rues

Divvying up Space: Housing Segregation and National Identity in Early Twentieth-Century Montréal - Sweeny, Robert C. H. (Sharing Spaces: Essays in Honour of Sherry Olson, 2020)
Keywords: Locataires; Logement; Quartiers

A Heuristic Archive: Jean-Paul Gill's Red Light Photographs - Guillaume, Philippe (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Archives; Patrimoine; Photographie; Quartiers; Saint-Laurent (quartier)

Lutter pour l’Église et la patrie tout en se récréant. Le cercle Langevin de l’ACJC, 1910-1920 - Warren, Jean-Philippe (Études d'histoire religieuse, 2020)
Keywords: Association catholique de la jeunesse canadienne-française (ACJC); Hochelaga (quartier); Quartiers

Les premières maisons shoebox montréalaises de Rosemont et de Villeray - Gaudreau, Guy (Urban History Review / Revue d'histoire urbaine, 2021)
Keywords: Quartiers; Rosemont; Villages; Villeray

Le haut des côtes était la zone. Le nord-est d'Ahuntsic entre 1932 et 1944 - Campeau, André (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Keywords: Ahuntsic; Logement; Pauvreté; Quartiers

Le docteur Ananie-Joseph Millier, un notable rosemontois méconnu - Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2021)
Keywords: Logement; Médecine; Quartiers; Rosemont

Une famille pionnière de la rue Dandurand: celle de George Ineson - Guilbault, Normand; Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2021)
Keywords: Famille; Logement; Quartiers; Rosemont

Photogenic Montreal: Activisms and Archives in a Post-Industrial City - Langford, Martha; Sloan, Johanne (McGill-Queen's / Beaverbrook Canadian Foundation Studies in Art History Series, 2021)
Keywords: Conservation; Patrimoine; Photographie; Quartiers

Re-activations: Alain Chagnon’s Plateau-Mont-Royal in Translation - Langford, Martha (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Photographie; Plateau Mont-Royal; Quartiers

Sharing Montréal’s Village Gai - Podmore, Julie A. (Sharing Spaces: Essays in Honour of Sherry Olson, 2020)
Keywords: Arrondissements; Quartiers; Ville-Marie (arrondissement)

Saint-Louis-Du-Mile-End. De la campagne à la ville (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
Keywords: Chemins de fer; Institution des sourds-muets; Logement; Mile End; Soeurs de la Providence

Petite histoire du Cercle de Fermières de Montréal-Nord - Savard, Marielle (Il était une fois...Montréal-Nord, 2022)
Keywords: Clubs; Femmes; Montréal-Nord; Quartiers

Gender and Social Relations in the City above the Hill - Sweeny, Robert C.H. (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Femmes; Golden Square Mile; Quartiers

Les découpages territoriaux de Rosemont-La Petite-Patrie (et du Plateau Mont-Royal) - Bur, Justin (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2021)
Keywords: Côtes; Plateau Mont-Royal; Quartiers; Rosemont

Grossières indécences: pratiques et identités homosexuelles à Montréal, 1880-1929 - Dagenais, Dominic (Études d'histoire du Québec / Studies on the history of Quebec, 2020)
Keywords: Clubs; Criminalité; Enfants; Police; Quartiers

"Un petit pouvoir": The Compagnie des jeunes Canadiens, Animation Sociale, and Citizens’ Committees in Little Burgundy, Montreal, 1967-74 - Langford, Will (The Global Politics of Poverty in Canada. Development Programs and Democracy, 1964-1979, 2021)
Keywords: Groupes populaires; Pauvreté; Petite-Bourgogne; Quartiers

« Nous ne parlerons pas de la guerre » : la participation oubliée de l’Université de Montréal à la Seconde Guerre mondiale - Walling, Jeremy John (Cahiers d'histoire, 2022)
Keywords: Guerre; Quartier latin (Le); Université de Montréal; Étudiants

« Others of more entreprise »: Thomas Morland and the Formation of Montreal Rolling Mills, 1858-1868 - Mathieu, Jean-Philip (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Montreal Rolling Mills; Quartiers

Un territoire à habiter et à aménager (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Keywords: Ahuntsic; Cartierville; Logement; Quartiers; Sault-au-Récollet

"Une démocratie quotidienne": The Compagnie des jeunes Canadiens, Animation Sociale, and Workers’ Activism in Saint-Henri, Montreal, 1967-74 - Langford, Will (The Global Politics of Poverty in Canada. Development Programs and Democracy, 1964-1979, 2021)
Keywords: Groupes populaires; Pauvreté; Quartiers; Saint-Henri; Travail

Luttes pour le droit au logement sur le Plateau - Vallée, Bernard (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2021)
Keywords: Crise; Groupes populaires; Logement; Plateau Mont-Royal; Quartiers

Marriage, Proprety, and the Law in a Square Mile Family: The Case of Annie Stevenson Anderson vs David Morrice, 1884-1885 - Gossage, Peter; Moore, Lisa (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Femmes; Golden Square Mile; Mariage; Quartiers; Tribunaux

La Ligue ouvrière catholique et la naissance de la paroisse Saint-André-Apôtre (première partie) - Ménard, Céline (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Ahuntsic; Famille; Jeunesse ouvrière catholique (JOC); Ligue ouvrière catholique; Logement; Quartiers

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

Soutien et entraide. Les mouvements coopératifs et communautaires du Plateau de 1970 à 2000 (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2021)
Keywords: Clinique des citoyens de Saint-Jacques; Cyclisme; Groupes populaires; Logement; Plateau Mont-Royal; Quartiers

Une belle histoire de coopération qui se poursuit - Archambault-Malouin, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Ahuntsic; Arrondissements; Cartierville; Coopérative d'habitation de Montréal; Domaine Saint-Sulpice; La Familiale; Logement; Quartiers

"Ils ne sont plus le peuple qu’ils étaient hier": la culture ouvrière à Montréal-Est au moment de la Confédération - Petitclerc, Martin; Bellavance, Claude; St-Hilaire, Marc (Le fait urbain, 2020)
Keywords: Cartier, Georges-Étienne; Lanctôt, Médéric; Montréal-Est; Partis politiques; Quartiers; Rouges; Saint-Jacques; Saint-Louis; Sainte-Marie; Travail; Élections